Analysis of Political Education and Democracy Theory: Pattern of Political Recruitment in the Leadership Council of the Partai Keadilan Sejahtera at the Natuna Regency Level - Mukmin Pohan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Political parties based on statutory arrangements, namely Law No. 2 of 2011 concerning Political Parties, regulates the functions of political parties, one of which is political recruitment. Of course, this arrangement is governed by the cadre section, without cadre formation it means nothing, political parties need a renewal of generations to renew their capacity to run political parties. The position in Indonesia's political development, especially in Natuna Regency, Riau Archipelago, must display quality leaders to manage the survival of the party. For example, the Prosperous Justice Party or in short PKS has pretty good electability in Natuna Regency. The PKS political recruitment process is regulated in statutes and bylaws intended for Indonesian citizens to regenerate party members. This study aims to determine the process of political recruitment of the Regional Leadership Council of the Prosperous Justice Party of Natuna Regency in selecting cadres for political positions and party positions and to find out what factors are the basis for determining political recruitment. The research used by the author is a qualitative research with descriptive method through an inductive approach. The author uses primary data and secondary data to obtain research data. Primary data comes from interviews conducted with informants while secondary data comes from KPU Regulation Number 20 of 2018 concerning PKS AD/ART, requirements for prospective legislative candidates, Management Structure of the Prosperous Justice Party Regional Leadership Council in Natuna Regency. Collecting data using interview techniques, qualitative observation and documentation. Results/Findings: The results of the study show that the recruitment system created by the Prosperous Justice Party in Natuna Regency is open recruitment by providing opportunities for all citizens to compete in the selection process. Then the determining factors in the political recruitment of the Regional Leadership Council of the Prosperous Justice Party in Natuna Regency were personality, party ideology and finances. Everyone who fulfills the requirements has the same opportunity to compete in both political and administrative positions. So, every candidate for the Prosperous Justice Party public office is decided by the Prosperous Justice Party DPD in Natuna Regency. According to Rush and Althoff, the pattern of PKS recruitment in determining legislative candidates for elections is closed.